Geochemical and ecotoxicological assessment for estuarine surface sediments from Southern Brazil - Rodrigues, Sarah K.; Abessa, Denis Moledo de Souza; Machado, Eunice C. (Elsevier, 2013)
Sediments from Guaratuba Bay (PR, Brazil), a marine protected area, were collected and evaluated for geochemistry and toxicity. High levels of P and acute toxicity were observed in some samples. Concentrations of Cu, Cd, Pb and Zn were relatively low; however, Cd levels eventually exceeded Threshold Effect Level. Toxicities were associated to nutrients and metals enrichment. Results suggest that impacts are incipient and occur only at specific sites, associated to multiple contamination sources. Despite sediments quality seems to range between good and fair, attention is required to land-use planning around Guaratuba Bay and controlling local pollution sources. © 2013 Elsevier Ltd. All rights reserved.
Keywords: Echinometra lucunter; Eutrophication; Guaratuba bay; Heavy metals; Nitrogen; Organic carbon; Phosphorous; Tiburonella viscana